1993
DOI: 10.2307/3578192
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Extracellular Adenosine Induces Radioprotective Effects in Mice

Abstract: The radioprotective effectiveness of the elevation of extracellular adenosine induced in mice by the combined administration of dipyridamole, a drug inhibiting the cellular uptake of adenosine, and adenosine monophosphate, a soluble adenosine pro-drug, was evaluated. Based on survival studies, endogenous hemopoietic spleen colony formation, and the postirradiation behavior of bone marrow granulocyte-macrophage colony-forming cells (GM-CFC), it was demonstrated that the combined administration of dipyridamole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…It stimulates the proliferation and differentiation of hematopoietic progenitors and also controls the functional activities of neutrophils and macrophages (Ikebuchi et al, 1988;Itoh et al, 1992). Our results are supported by those of Pospisil et al (1993Pospisil et al ( , 1995Pospisil et al ( , 1998, who showed that administration of adenosine monophosphate (AMP) combined with dypyridamole and G-CSF, prior to radiation, led to a radioprotective effect by the stimulation of haematopoiesis in the bone marrow and spleen of treated mice. The chemoprotective feature of the A3AR agonists is associated with other cytoprotective characteristics of these compounds.…”
Section: A3 Adenosine Receptor Agonists Inhibit Colon Carcinoma G Ohasupporting
confidence: 90%
“…It stimulates the proliferation and differentiation of hematopoietic progenitors and also controls the functional activities of neutrophils and macrophages (Ikebuchi et al, 1988;Itoh et al, 1992). Our results are supported by those of Pospisil et al (1993Pospisil et al ( , 1995Pospisil et al ( , 1998, who showed that administration of adenosine monophosphate (AMP) combined with dypyridamole and G-CSF, prior to radiation, led to a radioprotective effect by the stimulation of haematopoiesis in the bone marrow and spleen of treated mice. The chemoprotective feature of the A3AR agonists is associated with other cytoprotective characteristics of these compounds.…”
Section: A3 Adenosine Receptor Agonists Inhibit Colon Carcinoma G Ohasupporting
confidence: 90%
“…To the best of our knowledge, this is the first report that describes the presence of adenosine receptors on myeloid bone marrow progenitors, although such receptors have been defined on mature granulocytes, i.e., neutrophils (Cronstein, 1992). Pospisil et al (1993Pospisil et al ( , 1995Pospisil et al ( , 1998 showed that administration of adenosine monophosphate (AMP) combined with dipyridamole and G-CSF, prior to radiation, led to a radioprotective effect by the stimulation of hematopoiesis in the bone marrow and spleen of the treated mice. Jackson et al (1978) and Epstein and Preisler (1984) treated mice with the antimetabolite 6-thioguanine and demonstrated that adenosine exerted a protective effect on myeloid progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed the significant role of the nonselective activation of adenosine receptors in stimulating hematopoiesis [e.g., [10][11][12][13][14]. Discrimination between the hematopoiesismodulating effects of the activation of individual adenosine receptor types was made possible when selective adenosine receptor agonists became available.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the above studies, the hematopoiesismodulating effects of the adenosine receptor agonists have been observed for both granulopoietic and erythroid lineages [10,11,13,15]. These results have been obtained from the levels in the peripheral blood or from the compartments of bone marrow precursor and committed progenitor cells.…”
Section: Introductionmentioning
confidence: 99%